Analisis Kebijakan Standar Mutu Kualitas Sarana dan Prasarana antar Wilayah - Wahida Purnama; Ahyar; Badrun (Mataram University, 2026)
Educational facilities and infrastructure constitute one of the main pillars in achieving the improvement of national education quality. This study aims to analyze the Policy of Quality Standards for Facilities and Infrastructure Across Regions, as well as to identify various supporting and inhibiting factors in its implementation. Using a qualitative approach through document study and educational policy analysis methods, this case study compares the conditions at MTsN 1 Lombok Barat and MTsN 4 Lombok Barat. The results of the study indicate a gap in facilities and infrastructure across regions. MTsN 1 Lombok Barat, as a flagship madrasah, has relatively met the standards with complete and representative facilities. On the other hand, MTsN 4 Lombok Barat, as a developing madrasah, faces significant limitations in terms of laboratories, libraries, sports fields, and the utilization of educational technology. The main inhibiting factors include a lack of facilities and infrastructure, financial constraints, and suboptimal management. As a solution, the policy of